2022
DOI: 10.3390/life12050762
|View full text |Cite
|
Sign up to set email alerts
|

CD103 Expression on Regulatory and Follicular T Cells in Lymph Nodes, Bronchoalveolar Lavage Fluid and Peripheral Blood of Sarcoidosis Patients

Abstract: (1) Background: Sarcoidosis is a chronic multisystem disorder of unknown aetiology, driven by a T-cell mechanism allowing T-cell attachment and transmigration through the endothelium, and endorsed by the expression of an integrin alpha-E beta-7 (CD103). This study aimed to analyse the different distribution and compartmentalisation of CD103 expression on T cell subsets in BAL, peripheral blood mononuclear cells (PBMC) and lymph nodes (LLN) from sarcoidosis patients. (2) Patients: We consecutively and prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
(42 reference statements)
3
9
0
Order By: Relevance
“…Moreover, CD8+CD103+ may be involved in the autoimmune process [47]. However, it should be noted that there is an imbalance in circulating, alveolar and lymph node CD8+CD103+ T cells in the development of sarcoidosis [48]. Similar to the CD31+ marker, it seems that our results regarding the possible prognostic role of the CD8+CD103+ marker are in indirect agreement with the results of other authors.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, CD8+CD103+ may be involved in the autoimmune process [47]. However, it should be noted that there is an imbalance in circulating, alveolar and lymph node CD8+CD103+ T cells in the development of sarcoidosis [48]. Similar to the CD31+ marker, it seems that our results regarding the possible prognostic role of the CD8+CD103+ marker are in indirect agreement with the results of other authors.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, CD8+CD103+ may be involved in the autoimmune process [43]. However, it should be noted that there is an imbalance in circulating, alveolar, and lymph node CD8+CD103+ T cells in the development of sarcoidosis [44]. Similar to the CD31+ marker, it seems that our results regarding the possible prognostic role of the CD8+CD103+ marker are in indirect agreement with the results of other authors.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, Th1-, Th17-, and Th17.1-like Tregs phenotypically mimicked conventional IFN-γ and IL-17-producting Th cells and expressed similar patterns of ‘homing’ molecules [ 46 , 73 ], including chemokine receptors that regulated Treg cell migration to the sites of inflammation [ 74 , 75 ]. It is known that circulating and BAL-associated CD4+ T cells that produce IFN-γ play an important role in sarcoidosis-associated inflammation and granuloma formation, just as serum and BAL from patients with sarcoidosis are characterized by the increased levels of IFN-γ [ 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Duhen et al suggested that the increased frequency of IFN-γ-producing Treg cells in patients with type-1 diabetes and multiple sclerosis could be a response to autoimmune inflammation in these patients [ 45 ]. Next, E.L. McClymont et al reported that FOXP3+ IFNγ+ Treg frequency was significantly increased in patients with type 1 diabetes compared to the control group [ 73 ]. Similarly, an effector memory Treg subset expressing HLA-DR, CCR4, CCR6, CXCR3, and GATA3 was increased in the high-risk group of patients with type 1 diabetes [ 74 ].…”
Section: Discussionmentioning
confidence: 99%